In a queer time and place: Transgender bodies, subcultural lives - Halberstam, Jack (J.) (New York University Press, 2005)
In a Queer Time and Place opens with a probing analysis of the life and death of Brandon Teena, a young transgender man who was brutally murdered in small-town Nebraska. After looking at mainstream representations of the transgender body as exhibited in the media frenzy surrounding this highly visible case and the Oscar-winning film based on Brandon's story, Boys Don’t Cry, Halberstam turns her attention to the cultural and artistic production of queers themselves. Halberstam examines the “transgender gaze,” as rendered in small art-house films like By Hook or By Crook, as well as figurations of ambiguous embodiment in the art of Del LaGrace Volcano, Jenny Saville, Eva Hesse, Shirin Neshat, and others. Halberstam then exposes the influence of lesbian drag king cultures upon hetero-male comic films, such as Austin Powers and The Full Monty, and, finally, points to dyke subcultures as one site for the development of queer counterpublics and queer temporalities. Considering the sudden visibility of the transgender body in the early twenty-first century against the backdrop of changing conceptions of space and time, In a Queer Time and Place is the first full-length study of transgender representations in art, fiction, film, video, and music. This pioneering book offers both a jumping off point for future analysis of transgenderism and an important new way to understand cultural constructions of time and place.
Keywords: 2000 à aujourd'hui; 2000-2009; LGBTQIA2+; amériques; approches et analyses; cinéma; communication; cours; discipline; fem1000; har4600; identités LGBTQIA2+; lit4700; personnes trans*; premier cycle; périodes historiques; queer; régions géographiques; thématiques; transféminisme; états-unis; études culturelles

The queer art of failure - Halberstam, Jack (J.) (Duke University Press., 2011)
The Queer Art of Failure is about finding alternatives—to conventional understandings of success in a heteronormative, capitalist society; to academic disciplines that confirm what is already known according to approved methods of knowing; and to cultural criticism that claims to break new ground but cleaves to conventional archives. Jack Halberstam proposes “low theory” as a mode of thinking and writing that operates at many different levels at once. Low theory is derived from eccentric archives. It runs the risk of not being taken seriously. It entails a willingness to fail and to lose one’s way, to pursue difficult questions about complicity, and to find counterintuitive forms of resistance. Tacking back and forth between high theory and low theory, high culture and low culture, Halberstam looks for the unexpected and subversive in popular culture, avant-garde performance, and queer art. Halberstam pays particular attention to animated children’s films, revealing narratives filled with unexpected encounters between the childish, the transformative, and the queer. Failure sometimes offers more creative, cooperative, and surprising ways of being in the world, even as it forces us to face the dark side of life, love, and libido.
Keywords: LGBTQIA2+; amériques; approches et analyses; cours; fem1000; genre; har4600; identités LGBTQIA2+; lit4700; premier cycle; queer; ressource en ligne; régions géographiques; thématiques; états-unis; études culturelles